Paraesthesia of the lower lip as the presenting symptom of an acoustic neuroma: a case report. (30th May 2016) - Mann, L.; Moore, R.
Abstract: This case report describes a patient referred to secondary care from their General Dental Practitioner, who presented with paraesthesia to the left side of the lower lip. He was subsequently found to have an acoustic neuroma. The case aims to reinforce the seriousness of what could be seen as trivial findings to a patient, and the urgency of referral for further investigation.